Analysis Of The Environmental And Health Impacts Of The Area Affected By Tofu Liquid Waste In The Tofu X Home Industry In Pangkalan Kerinci Barat Village In 2020: Analysis Of The Environmental And Health Impacts Of The Area Affected By Tofu Liquid Waste In The Tofu X Home Industry In Pangkalan Kerinci Barat Village In 2020 - Ummi Khomarisah; Hastuti Marlina; M. Kamali Zaman (Progam Studi Kesehatan Masyarakat STIKes Hang Tuah Pekanbaru, 2021)
Home Industry Tofu X Established in 2002 and this business has existed from generation to generation until now. Tofu is a food made from fermented soybeans and extracted the juice. In general, the process of making tofu includes soaking soybeans for several hours, milling soybeans, boiling the results of milled soybeans, filtering, clumping soybean slurry using vinegar, molding and cutting. In the tofu industrial wastewater, there are organic materials in the form of 40-60% protein, 25-50% carbohydrates and 10% fat. If it is increasing, the volume will increase. The purpose of this study is to determine the Environmental and Health Impact Analysis of the Affected Areas of Tofu Liquid Waste in the Home Industry Tofu X Pangkalan Kerinci Barat Urban Village in 2020. This type of research is qualitative analytic by conducting in-depth interviews and direct observation. as well as laboratory tests for parameters BOD, COD and DO. The result of this research is that the waste treatment process has not been implemented in accordance with KepMenLH No. 51 of 1995 concerning the quality standard of liquid waste for tofu home industry. So that the resulting tofu wastewater is discharged directly into the pipelines leading to the river with BOD, COD and DO content which have not met the water quality standards set by the government PP No. 82 of 2001 and causing the river to be polluted, emitting a pungent odor and disturbing the comfort of the surrounding community. So a wastewater treatment plant (IPAL) is needed to treat water before it is discharged into the waters.